Content analysis of values deputed in the music curriculum of the public elementary schools in Manila - Aquino, Joselita Esguerra (1977)
This study was undertaken in recognition of education's important commitment in developing values among people particularly among school children. This was conducted to find out what values are depicted in the music curriculum of the public elementary schools in Metro Manila. From five important documents which, if considered together, form an adequate source of a comprehensive listing of values, the researcher was able to arrive at a set of 37 specific values categorized into 7 value clusters namely: economic, social, ethical, civic, cultural, aesthetic and spiritual values. Music objectives and instructional materials were taken from the music curriculum guides and hand-outs prepared and issued by the Music and Arts Education Services of the Division of City Schools, Manila. Fifty percent of the total number of data compiled for each grade level was taken for study by systematic sampling.